Correlation between Family Incomes and Students English Achievement at MTs Nurul Hidayah Malang - Ainul Yaqin Abdillah; Hanif Maulaniam Sholah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
AbstractThe purpose of this research was to find a relationship between family income and student’s English achievement at MTs Nurul Hidayah Bantur. In this study, the author uses quantitative analysis techniques in which he performs a series of tests including: validity test, reliability test, descriptive statistic test, normality test, linearity test, chi square test to test hypotheses, and coefficient of determination test to find out how much influence between variables tested.The results showed that there were 41 respondents in this study, of which all came from class VIIB and VIIIB, the instrument validity test showed that of the 14 instruments tested were declared valid because all of them had a sig 2 tailed value below 0.05. The reliability test is at .924 with the meaning that the instrument that the author uses is in reliable condition, in the above test the author uses a shadow sample of 20 children. The normality test got a 2-tailed sig value at .200, with a meaning of .200 < 0.05 then it was stated that the data distribution was normally distributed. Linearity test gave a sig deviation from linearity value at .186 with a meaning of .186 > 0.05 with the meaning that the independent variable and the dependent variable has a linear relationship. Chi square test gets a value of .000 with the meaning that .000 < 0.05 then H1 is accepted and H0 is rejected, there is an influence between family incomes and student's English achievement. This test is also supported by the results of the coefficient of determination test which is at number .542 with the meaning that the independent variable affects the dependent variable by 54.2%.Keywords: Correlation, Family Incomes, and Student’s English Achievement